Pengaruh Pemberian Aromaterapi Lemongrass Dalam Mengurangi Mual Muntah Pada Ibu Hamil Trimester I di Wilayah Kerja Puskesmas Cimarga Tahun 2024 - Rini Rini; Mariyani Mariyani (Universitas Pahlawan Tuanku Tambusai, 2025)
Emesis gravidarum can occur in the morning so it can disrupt the activities of pregnant women. The main cause is decreased progesterone levels and high fluctuations in hCG levels. One non-pharmacological way that can reduce nausea and vomiting is by administering lemongrass aromatherapy.to determine the effect of providing lemongrass aromatherapy in reducing nausea and vomiting in first trimester pregnant women in the Cimarga Community Health Center Work Area in 2024.pre-experimental design with one group pretest-posttest design. The research sample was 30 respondents from first trimester pregnant women experiencing emesis gravidarum using a purposive sampling technique. The research instrument used the PUQE-24 questionnaire observation sheet. The data is primary data analyzed using the paired sample t-test.univariate analysis of nausea and vomiting in first trimester pregnant women before administering lemongrass aromatherapy with an average of 9.63 (moderate), afterward with an average of 5 (mild), an average difference of 4.63 was obtained. The results of the bivariate analysis showed the effect of giving lemongrass aromatherapy in reducing nausea and vomiting in pregnant women in the first trimester with a p value = 0.000.There is an effect of giving lemongrass aromatherapy in reducing nausea and vomiting in pregnant women in the first trimester. Health workers are expected to be able to apply lemongrass aromatherapy in treating nausea and vomiting in pregnant women in the first trimester so that apart from being cheap, there are no side effects so that it is safe for mothers to give.